Mucinous Cystic Neoplasm of the Liver Mimicking as Hydatid Cyst: A Case Report - Ranjita Panigrahi; Ajit Kumar Singh; Arlene Bhuyan; Amaresh Mishra; Subrat Kumar Sahu (Journal of Clinical and Diagnostic Research)
Mucinous Cystic Neoplasms (MCNs) of the liver are rare cystic tumours, accounting for less than 5% of all liver cysts. They usually arise in the liver parenchyma and less frequently in the extrahepatic bile duct. Women in their 5th and 6th decades are predominantly affected. Various liver cystic lesions, such as hydatid cysts, simple cysts and endometriotic cysts, can mimic this rare entity radiologically. The present case involved a 38-year-old female who was admitted with chief complaints of skin rash, swelling in the face and feet, pain in all limbs, and abdominal distension for six months. She experienced significant weight loss and was unable to perform daily activities. Ultrasonography (USG) of the abdomen showed a well-defined multiloculated cyst in segment IV of the liver, which was further confirmed by a Contrast-enhanced Computed Tomography (CECT) scan. The patient underwent laparoscopic surgery based on the radiological diagnosis of a hydatid cyst. Histopathological (HP) study of the cyst wall revealed a diagnosis of MCN, which was further confirmed by Immunohistochemistry (IHC). The postoperative period remained uneventful. Complete surgical excision is the treatment of choice over conservative management and partial excision, as it has low recurrence rates and a good survival rate. Due to its rare presentation and the varied number of radiological differential diagnosis, it often leads to delayed or misdiagnosis. Authors hereby report the present case along with a brief review of the literature to increase radiological and clinical awareness, which is essential to keep MCN as a differential diagnosis during the initial evaluation of any cystic lesion of the liver.